(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the modern world a new danger has appeared before humanity, which instilled fear in the consciousness of people. Such phenomena as radicalism, terrorism and extremism are the main three problems for any state. Each country tackle with these phenomena using peculiar methods. The media play an important role in this tackle. They form the image of the radicals, write news about them. Generally, they are the main ideologicaweapons of the state. Therefore, this article analyzes articles in the media on such phenomena as radicalism and terrorism. There were 4 information and 1 analytic, 3 Russian-language and 2 Kazakh-language medias were reviewed. The focus of the study was to explore the ways of recruitment, general values of people with radical views, causes of radicalization, socio-demographic (gender, age, education) features and geography of distribution of radicalism. In addition, the article discusses the style of describing the personalities of radicals in the media, because this affects to the perception and formation of an image of radicals in public opinion.In the future, the results of the research can be used to prepare programs to counter religious extremism and terrorism, information groups for clichés, as well as to prepare lectures on such subjects as religious studies, history, political science and sociology of religion. Key words: radicalism, radical, media, terrorism, radicalization.